Karakteristik Mikroemulsi Minyak Atsiri Daun Cengkeh Pada Rasio Campuran Surfaktan dan Minyak Atsiri Daun Cengkeh (Syzygium aromaticum) - Rajagukguk, Jopi Deri P H; Suhendra, Lutfi; Hartiati, Amna (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2024)
Clove (Syzygium aromaticum) is an herbal plant which all parts starting from the roots, stems, leaves and flowers contain essential oils. Clove leaf essential oil has an eguanol concentration of (46.69%-64.91%) which functions to fight bacteria that enter the body. This research aims to determine the effect of surfactant and clove leaf essential oil mixtures on the characteristics of clove leaf essential oil microemulsions and determine the best surfactant and clove leaf essential oil mixtures to produce clove leaf essential oil microemulsions. This research used Randomized Group Design, with surfactant:clove leaf essential oil ratio with 10 levels, 100:0; 98:2; 96:4; 94:6; 92:8; 90:10; 88:12; 86:14; 84:16 and 82:18. The best microemulsion is the one with highest concentration of clove leaf essential oil. The best microemulsion was tested for stability against pH and dilution during 8 weeks storage. The turbidity index value was tested every 2 weeks. The deterioration rate was calculated using linear regression analysis to determine the stability of clove essential oil microemulsion. The results showed that the ratio of surfactant and clove leaf essential oil mixture had a very significant effect (P<0.01) on the characteristics of clove leaf essential oil microemulsion. The ratio of surfactant and clove leaf essential oil 88:12 is the best treatment to produce clove leaf essential oil microemulsion with transparent appearance characteristics, turbidity index value before 0.223 ± 0.003%; after centrifugation 0.189 ± 0.003%; particle size 17.1 ± 8.3 nm, and the largest droplet size is 14nm and stable for 8 weeks of storage.